Sub-surface drip fertigation improves seed cotton yield and monetary returns - Singh, Kulvir; Singh, Prabhsimran; Singh, Manpreet; Mishra, Sudhir Kumar; Iqbal, Rashid; Al-Ashkar, Ibrahim; Habib-ur-Rahman, Muhammad; El Sabagh, Ayman (Frontiers in Plant Science, 2022)
Surface flood (SF) method is used to irrigate cotton in India, which results in huge wastage of water besides leaching of nutrients. This necessitates the adoption of efficient management strategies to save scarce water without compromising the yield. Therefore, a 2-year field investigation was conducted under two climatic regimes (Faridkot and Abohar) to study the effect of sub-surface drip fertigation (SSDF) on seed cotton yield (SCY), water productivity, nitrogen use efficiency (NUE), and economic parameters in comparison with SF and surface drip fertigation (SDF). The field experiment had a total of eight treatments arranged in a randomized complete block design. Three levels of sub-surface drip irrigation [(SSDI); i.e., 60%, 80%, and 100% of crop evapotranspiration (ETc)] and two N fertigation levels [100% recommended dose of nitrogen (RDN; i.e., 112.5 kg N ha-1) and 75% RDN] made up six treatments, while SF (Control 1) and SDF at 80% ETc (Control 2), both with 100% of RDN, served as the controls. Among irrigation regimes, the SSDI levels of 80% ETc and 100% ETc recorded 18.7% (3,240 kg ha-1) and 21.1% (3,305 kg ha-1) higher SCY compared with SF (2,728 kg ha-1). Water use efficiency under SF (57.0%) was reduced by 34.2%, 40.8%, and 38.2% compared with SSDI’s 60 (76.5%), 80 (80.3%), and 100% ETc (78.8%), respectively. Among fertigation levels, NUE was higher by 19.2% under 75% (34.1 kg SCY kg-1 N) over 100% RDN (28.6 kg SCY kg-1 N), but later it also registered 11.9% higher SCY, indicating such to be optimum for better productivity. SSDF at 80% ETc along with 112.5 kg N ha-1 recorded 26.6% better SCY (3455 kg ha-1) and 18.5% higher NUE (30.7 kg SCY kg-1 N) over SF. These findings demonstrate that the application of SSDF could save irrigation water, enhance SCY, and improve the farmers’ returns compared with SF. Therefore, in northwestern India, SSDF at 80% ETc along with 112.5 kg N ha-1 could be a novel water-savvy concept which would be immensely helpful in enhancing cotton productivity.